2009
DOI: 10.3844/ajassp.2009.1880.1884
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics of Compost and Humic Acid from Sago Waste (Metroxylon sagu)

Abstract: Problem statement: Agriculture waste such as Sago Waste (SW) has a potential to cause pollution either on land or in water. In order to reduce this problem, a study was conducted to investigate the effect of three different treatments on the chemical characteristics of compost and humic acid from SW. Approach: The study had three treatments which were: T1: SW (80%) + chicken feed (5%) + chicken dung slurry (5%) + molasses (5%) + urea (5%), T2: SW (80%) + chicken feed (10%) + chicken dung slurry (5%) + molasses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…The observed prolonged broad and greater range of thermophilic temperatures in chimato compost piles Td0, Td20 and Td40 are attributable to their high initial C/N ratios (C/N ratio 66:1, 41:1 and 37:1 respectively; C/N> 31:1) of the blend that induced slow microbial decomposition process because their substrate possessed abundant carbon in agreement to reports by WSU (2010), Petrus et al (2009) andTani (2009). It is suggested that maize stalks provided the large quantities of high carbon content cellulosic materials (lignin) whose oxidation and digestion generate large amounts of heat that made Td0, Td20 and Td40 to experience prolonged high temperatures.…”
Section: Effect Of T Diversifolia Content On Heat Built Upsupporting
confidence: 77%
See 3 more Smart Citations
“…The observed prolonged broad and greater range of thermophilic temperatures in chimato compost piles Td0, Td20 and Td40 are attributable to their high initial C/N ratios (C/N ratio 66:1, 41:1 and 37:1 respectively; C/N> 31:1) of the blend that induced slow microbial decomposition process because their substrate possessed abundant carbon in agreement to reports by WSU (2010), Petrus et al (2009) andTani (2009). It is suggested that maize stalks provided the large quantities of high carbon content cellulosic materials (lignin) whose oxidation and digestion generate large amounts of heat that made Td0, Td20 and Td40 to experience prolonged high temperatures.…”
Section: Effect Of T Diversifolia Content On Heat Built Upsupporting
confidence: 77%
“…The blending composition probably provided the organic resources of Td0, Td20 and Td40 with large initial C/N ratio (67:1, 41:1, 37:1) and organic resources of Td80 and Td100 with lower initial C/N ratio (15:1, 10:1) such that Td0, Td20 and Td40 organic resources possessed large quantities of carbon atoms without corresponding provision of nitrogen atoms for microbes to use as source of energy and as building materials of their structures respectively. As such, microorganisms slowly digested the abundant carbon atoms in the organic resource by using and/or reusing their stored limited nitrogen to burn large quantities of carbon atoms for a longer period supporting findings by Petrus et al (2009) and Tani (2009) that slow and passive microbial activities are experienced in compost piles with initial C/N ratio of greater than 30:1. Thus, the process prolonged exothermic decomposition reaction that induced the observed high-prolonged temperatures (heat built-up) as well as broad and greater range of compost heat built-up in chimato composts Td0, Td20 and Td40.…”
Section: Effect Of T Diversifolia Content On Heat Built Upsupporting
confidence: 49%
See 2 more Smart Citations
“…Organic solvents possess lower dielectric constant than the inorganic solvents. Generally, amylase is extracted in organic solvents (Petrus et al, 2009) such as ethanol, methanol, glycerol. But during our investigation, CaCl 2 acted as the best solvent that might be attributed to some stimulatory effect of CaCl 2 on amylase extraction and activity.…”
Section: Discussionmentioning
confidence: 99%